Study of Residents' Lifestyles Viewed from the Perspective of Millennial Generation Residential Preferences in Medan Johor District Housing - Khairunnisa, Nabila; Nirfalini Aulia, Dwira; Zahrah, Wahyuni (Lafadz Jaya Publisher, 2024)
Urban life is increasingly becoming the main focus in the development of urbanization in various countries, including Indonesia. With rapid economic growth, the millennial generation, which is the dominant group in the urban population, has a significant role in determining lifestyle trends, especially regarding residential preferences. This research aims to examine the lifestyle of housing residents in Medan Johor District with a focus on the residential preferences of the millennial generation. This research method uses a qualitative approach with data collection techniques through questionnaires and observation. The variables in this research can be divided into variable as well as demographic factors that may influence residential preferences (such as: age, income, marital status, etc.). The research results show that the millennial generation tends to have housing preferences that prioritize affordability, transportation accessibility and an environmentally friendly environment. The research results show that there is a connection between millennial lifestyles and residential preferences. Statistical analysis shows a significant relationship between lifestyle factors and choice of residence.These findings have significant implications for housing developers and related stakeholders in designing and developing housing that suits the preferences and lifestyle of the millennial generation in Medan Johor District with a sample of 6 housing complexes.